Energy Consumption and Sustainable Economic Welfare: New Evidence of Organization of Petroleum Exporting Countries - Azami, Somayeh; Almasi, Shabnam (International Journal of Energy Economics and Policy, 2020)
This paper examines the relationship between energy consumption and sustainable economic welfare in Organization of Petroleum Exporting Countries. Initially, the index of sustainable economic welfare is calculated followed by an investigation of the relationship between energy consumption and sustainable economic welfare in these countries. The calculation of the index of sustainable economic welfare reveals the most important beneficial component and the most important cost component of ISEW is adjusted personal consumption and energy depletion, respectively. The estimated results based on the Westerlund (2007) test and considering cross-sectional dependence indicate that there is a long run relationship between energy consumption and sustainable economic welfare. Granger's causality test results indicated a unidirectional causality running from sustainable economic welfare to energy consumption. This result has implications for energy and environmental policy makers; energy conservation policy will be useful in improving the quality of environment and it does not have adverse impact on their sustainable economic welfare. Keywords: Energy Consumption, Sustainable Economic Welfare, Energy Conservation Policy, Quality of environment, OPEC JEL Classifications: Q43, Q56, I31 DOI: https://doi.org/10.32479/ijeep.9435